DESIGN ANALYSIS OF FLUID-FLOW THROUGH PERFORATED PLATES - Celik, Nevin; Bayazit, Yilmaz; Turgut, Emre; Sparrow, Ephraim M. (Vinca Inst Nuclear Sci, 2018)
The performance of the perforated plates in fluid-flow applications is evaluated by measuring the pressure drop of the working fluid. The purpose of this investigation is to determine how different parameters affect the capability of the perforated plates and modify the design by using a design of experiment analysis, namely Taguchi method for optimization. The flow characteristics, which were obtained by the CFD software package ANSYS-CFX, were used for this analysis. The design parameters which affect the pressure loss are Reynolds number (A), porosity (B), non-dimensional thickness of the plate (C), and hole pattern (D). The level of importance of the design parameters are determined by use of analysis of variance method. According to the analysis, the optimum values are obtained for the case A8B2C2D1 (Re = 15000, porosity = 50.3, t / D = 1, and staggered hole). The most effective design parameter on the results is found as porosity (92%), while the least effective is the hole pattern (0.2%). A special dividend of this work was to demonstrate the capabilities of the Taguchi method as a powerful means of increasing the effectiveness of numerical simulation.
Keywords: perforated plates; CFD; Taguchi; design of experiment